The complete mitochondrial genome of the Antarctic marbled rockcod, Notothenia rossii (Perciformes, Nototheniidae) - Euna Jo; Yll Hwan Cho; Seung Jae Lee; Eunkyung Choi; Jeong-Hoon Kim; Young Min Chi; Jin-Hyoung Kim; Hyun Park (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Notothenia rossii was obtained using PacBio Sequel long-read sequencing platform. The mitogenome of N. rossii was circular form and 18,274 bp long, which consists of 13 protein-coding genes, 24 tRNAs, 2 rRNAs, and non-coding control region. Particularly, we found duplicated tRNAThr and tRNAPro in addition to the typical 22 tRNAs. The phylogenetic tree revealed that N. rossii was most closely related to N. coriiceps among species in the Nototheniidae clade within the suborder Notothenioidei.